Evaluating scenarios for twenty-first-century Australian settlement planning: a Delphi study with planning experts. Issue 3 (3rd July 2022) - Bolleter, Julian; Edwards, Nicole; Freestone, Robert; Nichols, David; Hooper, Paula
ABSTRACT: This paper presents findings from a national survey of Australian planning experts examining future settlement patterns and locations at the continental scale. Collective judgement supported efforts to achieve population decentralisation and favoured three possible scenarios – Satellite Cities, Boosted Secondary Capital Cities, and East West Megaregions. The findings on preferred settlement pattern scenarios can inform future efforts to develop a national urban policy for Australia. This case study can also serve as a reference point to the over 160 countries worldwide that are developing, implementing, or evaluating national urban policies in support of global urban agendas.